Deep Learning sebagai Strategi Adaptif dalam Meningkatkan Kualitas Pendidikan Anak Usia Dini - Najiich, Muchammad; Titi Lestari (Prodi PIAUD STAI AL-GAZALI BONE, 2026)
This study aims to analyze the implementation of deep learning as an adaptive strategy to improve the quality of early childhood education. A descriptive qualitative literature review was employed using thematic mapping of relevant studies published between 2021 and 2025. The findings indicate that most early childhood educators have a limited understanding of deep learning, commonly equating it with the use of digital media. Learning practices and lesson plans remain one-directional and focus on memorization, which hinders children’s reflective thinking skills. However, exploratory activities such as gardening and role play show strong potential to foster critical thinking, autonomy, and self-reflection in children. Key supporting factors include visionary school leadership, collaborative culture, and family involvement. In conclusion, deep learning can become a transformative pedagogical approach if supported by continuous teacher training and institutional reinforcement.